An Error Analysis on The Use of Simple Present Tense in The Students’ Descriptive Text Among the Seventh Grade of Smp Swasta Pangeran Antasari Medan - Laia, Joshua Hati Abdi (ELT (English Language Teaching Prima Journal), 2024)
This study is aimed at finding and analyzing errors in the use of simple present tense in descriptive texts written by seventh graders of SMP Swasta Pangeran Antasari Medan. The approach followed in this research was a qualitative method involving description and analysis. This data was collected through the students using tests that had been pre-prepared for them and interviews that were structured. In view of this, it is worth noting that there are only two main types of errors: intralingual errors and interlingual errors. These hindrances are caused by interference from their native language, Bahasa Indonesia thus making them disarrange sentences wrongly or even create new words. Meanwhile, intra-lingual errors, such as omission and addition, arise due to students' lack of understanding of English grammar rules. From the total 90 errors identified, omission errors were the most dominant with a percentage of 42.2%, followed by mis-formation (25.5%), mis-ordering (16.6%), and addition (15.5%). This study underscores the importance of more focused and interactive grammar teaching, as well as more frequent writing practice with constructive feedback to reduce errors in Simple Present Tense usage. The results are anticipated to enhance to standard of English language instruction in educational institutions, namely in the area of composing descriptive texts.